2003
DOI: 10.1108/01409170310783745
|View full text |Cite
|
Sign up to set email alerts
|

New developments in executive relocation practices

Abstract: 1997),"The changing face of relocation management", Facilities, Vol. 15 Iss 5/6 pp. 150-154 http:// dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Bright (2008) asserts that there are negative correlations between language skills, previous experience with that of socio-cultural adjustment. In this context, the findings contradict many previous studies, which have found that language skills and previous experience are most influential factors on three facets of socio-cultural adjustment (Andreason, 2003;Bhaskar Shrinivas et al,2004;Bird, Black & Stephens, 1989;Fenner, 2005;Garson, 2005;Hechanova et al,2003;Johnson et al,2006;Mendenhall & Oddou, 1985;Rushing & Kleiner, 2003;Sargent, 2002;Selmer, 2001;Selmer, 2005;Shaffer et al,1999;Shim, 2001;Von Glinow et al,2004).…”
Section: A Critical Overview On Socio-cultural Adjustment and Job Percontrasting
confidence: 98%
“…Bright (2008) asserts that there are negative correlations between language skills, previous experience with that of socio-cultural adjustment. In this context, the findings contradict many previous studies, which have found that language skills and previous experience are most influential factors on three facets of socio-cultural adjustment (Andreason, 2003;Bhaskar Shrinivas et al,2004;Bird, Black & Stephens, 1989;Fenner, 2005;Garson, 2005;Hechanova et al,2003;Johnson et al,2006;Mendenhall & Oddou, 1985;Rushing & Kleiner, 2003;Sargent, 2002;Selmer, 2001;Selmer, 2005;Shaffer et al,1999;Shim, 2001;Von Glinow et al,2004).…”
Section: A Critical Overview On Socio-cultural Adjustment and Job Percontrasting
confidence: 98%
“…However, we acknowledge that the model presented here is a work-in-progress and will evolve as research in this area develops. We feel that with the high costs of expatriate assignments and failure (Poe, 2002;Rushing & Kleiner, 2003), and with the number of expatriates increasing (Voigt, 2001), the issue of expatriate management will continue to be important. We hope that future research will continue to adopt the HCN perspective in other productive ways and advance our understanding of various psychological and social processes in MNEs.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have been discussing training, mentoring, and coaching to aid the transition back to the home environment for more than a decade (see Andreason & Kinneer, 2005;Cavusgil, Yavas, & Bykowicz, 1992;Forster, 2000;Hocking, Brown, & Harzing, 2007;Mezias & Scandura, 2005;Rushings & Kleiner, 2003;Swaak, 1997). More recently, scholars have raised concerns about wasted opportunities for transferring learning from foreign locations to the home environment and have called for supportive human resource (HR) practices to aid such transfers (see Andreason & Kinneer, 2005;Furuya, Stevens, Oddou, Bird, & Mendenhall, 2007;Harvey & Novicevic, 2006;Lazarova & Caligiuri, 2001;Lazarova & Tarique, 2005;Minbaeva, 2007;Stevens, Oddou, Furuya, Bird, & Mendenhall, 2006).…”
mentioning
confidence: 99%